Reproductive cycles in white Karaman ewes: comparison of ovarian hormone secretion and reproductive behavior in non-pregnant and pregnant ewes in semi-intensive conditions (Acta Scientiarum. Animal Sciences, 2018)
The objective of this study was to characterize the reproductive cycle both endocrinologically and behaviorally in ewes. Blood samples were analyzed by EIA for progesterone (P4), and RIA for estradiol in order to determine the breeding strategy of non-pregnant (n = 11) and pregnant (n = 9) White Karaman throughout the year in the Middle Anatolia (39.570N, 32.530W), Turkey. Estrous cycle lengths and estrous lengths were 18.36 ± 1.03 days and 35.16 ± 5.95 hours, respectively. The breeding season durations were 283 ± 63.36 days and 229.64 ± 63.74 days according to hormonal and behavioral data respectively (p £ 0.01). The highest and lowest data of estrous occurrence frequency was observed in October and June-July, respectively. P4 levels ranged from 0.01 to 9.0 ng mL-1 throughout the year and from 0.01 to 0.16 ng mL-1 during anestrous. Mean plasma estradiol levels were 8.42 ± 2.51 pg mL-1 during the estrous cycle. Postpartum anestrous durations were 134.8 ± 18.5 and 120.78 ± 29.89 days (n = 9) according to behavioral observation and hormonal data, respectively. P4 concentration for the months 1 – 5 of the gestation period ranged from 4.54 to 15.08 ng mL-1. P4 concentrations in 4th and 5th months of gestation were higher than the other months (p £ 0.01). White Karaman reproductive activity is characterized by an extended breeding season and their relatively insensitivity to photoperiod stimulation allows for efficient out of season lamb production.